VOTER BEHAVIOR IN ELECTION OF PRESIDENT AND VICE PRESIDENT 2019: (Phenomenological Study in Badur Village, Sumenep Regency) - Effendi, Ach (JURNAL SETIA PANCASILA, 2022)
This study aims to describe the activities of the Badur Village community in the 2019 Presidential and Vice Presidential elections in the form of forms of Badur Village community voter behavior in the 2019 Presidential and Vice Presidential elections. This study uses a qualitative approach based on phenomena, facts or information that uses an approach called the investigative approach. The data collection method in this study used observation, documentation and interview techniques. The data analysis used by the researcher refers to three steps, namely (1) data reduction, (2) data display, (3) verification. The results showed that voter behavior in Badur Village could be categorized into three types of behavior with varying percentages. The results show that the sociological type places the highest percentage at 40%, followed by a rational approach of 35% and a psychological 25%. The participation of the people of Badur Village in the election of the President and Vice President was very enthusiastic even though they were not registered in the formal campaign team and only a few people participated in political parties, while community participation in voting was extraordinary, around 92% of the people of Badur Village exercised their voting rights and This is the highest voter turnout since the direct presidential and vice presidential elections in 2004.